2013
DOI: 10.1021/ja309812z
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Adhesion to the Cell Membrane and Its Effect on Nanoparticle Uptake Efficiency

Abstract: ABSTRACT:The interactions between nano-sized particles and living systems are commonly mediated by what adsorbs to the nanoparticle in the biological environment, its "biomolecular corona", rather than the pristine surface. Here we characterise the adhesion towards the cell membrane of nanoparticles of different material and size, and study how this is modulated by the presence or absence of a corona on the nanoparticle surface. The results are corroborated with adsorption to simple model supported lipid bilay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
593
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 716 publications
(631 citation statements)
references
References 44 publications
33
593
2
3
Order By: Relevance
“…The ranking in cell fluorescence, on the other hand, must be interpreted with care. Certainly, a large part of the signal at these short exposure times may come from nanoparticles adsorbed to the outer cell membrane, as we have shown previously 4 . This is consistent with larger (G2/M) cells exhibiting a higher fluorescence than smaller (G1) cells.…”
supporting
confidence: 51%
“…The ranking in cell fluorescence, on the other hand, must be interpreted with care. Certainly, a large part of the signal at these short exposure times may come from nanoparticles adsorbed to the outer cell membrane, as we have shown previously 4 . This is consistent with larger (G2/M) cells exhibiting a higher fluorescence than smaller (G1) cells.…”
supporting
confidence: 51%
“…Lifetime of GFP in cell culture is found to be around 2ns, as seen in the lifetime distribution in Figure 1(f). This lifetime value is in consistent with published results [43,44]. By comparing the images shown in Figure 1, we can confirm that early endosomes in Hela cells have been well stained by GFP.…”
Section: Surface Plasmon Enhanced Energy Transfer Effectsupporting
confidence: 92%
“…Notwithstanding the limitation of our model with respect to a cellular membrane for which the structure is much more complex, we can state that both shear flow 60 and excess of proteins, which reduce NP surface free energy, 23,61 influence NP adhesion to lipid membranes when unspecific interactions are predominant. Overall, our results suggest that while the presence of hard corona flattens the interaction between NPs and model lipid bilayers, the associated soft corona affects the structure of the bilayer in a different way compared to free proteins.…”
Section: Discussionmentioning
confidence: 99%
“…22 Since the PC affects the properties of the NP surface, it has significant impact on the interaction between membrane and NPs. [23][24][25][26][27] Many studies are described in the literature where NP cellular uptake is related to the presence of a PC on the NPs in biological fluids, [28][29][30] in particular it has been shown that a key factor in NPs cellular uptake is their adhesion to the cell membrane that significantly affects their final uptake rates. 31 NP-cell membrane interaction is a complex dynamic process in which the environmental proteins are known to play an important multifaceted role: not only they adsorb onto the NP surface forming the PC, but also they compete with the NP in the interaction with the cell membrane.…”
Section: Introductionmentioning
confidence: 99%